1995
DOI: 10.1111/j.1476-5381.1995.tb16660.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by propofol (2,6 di‐isopropylphenol) of the N‐methyl‐D‐aspartate subtype of glutamate receptor in cultured hippocampal neurones

Abstract: 1 The effects of propofol (2,6 di-isopropylphenol) on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
116
1
4

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(123 citation statements)
references
References 39 publications
2
116
1
4
Order By: Relevance
“…It also has been reported that propofol inhibits N-methyl-Daspartate (NMDA) receptor in cultured hippocampal neurons. 24 Results of our present in vivo experiment show that propofol inhibited the Glu-induced vasomotor action not only in the RVLM but also in the DM. The latter structure has been shown repeatedly to contain neuronal cell bodies sharing vasomotor integration.…”
Section: Discussionmentioning
confidence: 50%
“…It also has been reported that propofol inhibits N-methyl-Daspartate (NMDA) receptor in cultured hippocampal neurons. 24 Results of our present in vivo experiment show that propofol inhibited the Glu-induced vasomotor action not only in the RVLM but also in the DM. The latter structure has been shown repeatedly to contain neuronal cell bodies sharing vasomotor integration.…”
Section: Discussionmentioning
confidence: 50%
“…Potentiation of glycine receptors by propofol has also been demonstrated in mouse spinal neurones (Hales & Lambert, 1991). Propofol inhibits whole cell currents activated by N-methyl-D-aspartate (NMDA) without affecting kainate-evoked currents in cultured mouse hippocampal neurones (Orser et al, 1995). Propofol also inhibits T-type and L-type voltage-dependent Ca2" channels in chick dorsal root ganglion neurones (Olcese et al, 1994), as well as KCl-evoked, and presumably Ca2" channelmediated, [3H]-noradrenaline release from human neuroblastoma cells .…”
Section: Discussionmentioning
confidence: 99%
“…This study is primarily focused on gaining a better understanding of the relative role (if any) of GABA tonic in producing depression of intrinsic neuronal excitability in neurons in intact acute brain slices, where the neuronal properties should be similar to in vivo. In the case of propofol, a widely used anesthetic, there are many sites of action that may affect intrinsic excitability, including effects on phasic (Trapani et al 2000) and tonic (Bai et al 2001) inhibition mediated by GABA A receptors (GABA A -Rs); sodium channels (Ratnakumari and Hemmings 1997;Rehberg and Duch 1999); potassium channels (Magnelli et al 1992); cation channels (I h ) (Higuchi et al 2003); calcium channels (Guertin and Hounsgaard 1999;Inoue et al 1999); glutamate channels (Orser et al 1995); and glutamate release (Ratnakumari and Hemmings 1997). Assuming that propofol suppresses intrinsic excitability, two critical questions emerge: is GABA tonic enhancement by anesthetics of sufficient magnitude to affect intrinsic excitability and given the existence of other proposed sites of propofol action that would affect intrinsic excitability, are effects on GABA tonic relatively dominant, relatively unimportant, or one contributor among many?…”
Section: Introductionmentioning
confidence: 99%